Weak Transitions Effect from First Excited States in Core of Massive Star in Pre-supernova Phase - Rocha, S. C.; Samana, A. R.; Dimarco, A. J.; Barbero, C. A.; dos Santos, M.; De Conti, C. (Brazilian journal of physics, 2025)
Massive stars in the pre-supernova stage are characterized by a compound core of chemical elements of the iron group, subject to nuclear reactions provided by the weak interaction. The rates at which these reactions occur, particularly the β -decay and the electron capture, influence the electron fraction in the core, and these particles are responsible for generating a degeneracy pressure that counteracts the gravitational collapse. We calculate electron capture and β - -decay rates for a set of 63 nuclei (previously adopted in Dimarco et al., J. Phys. G Nucl. Part. Phys. 28 121 2002) of relevance in the pre-supernova stage for transitions not only from the ground state but also considering first excited states in the parent nucleus, using the gross theory of beta decay (GTBD) associated to Brink’s hypothesis. The evolution of the electron fraction has been calculated using these weak interaction rates, and the results have been compared with other models, showing that transitions between low-lying first excited states and Gamow-Teller resonances can contribute at this stage of stellar evolution as the temperature and density increase.